Imaging anatomy. Ultrasound - Woodward, Paula J; Griffith, James F; Antonio, Gregory E; Ahuja, Anil T; Wong, K. T; Kamaya, Aya; Wong-You-Cheong, Jade (Elsevier, 2018)
Designed to help you quickly learn or review normal anatomy and confirm variants, Imaging Anatomy: Ultrasound, second edition, is the ultimate reference worldwide, keeping you current within the fast-changing field of ultrasound imaging through comprehensive coverage of sonographic anatomy for head and neck, musculoskeletal, abdomen and pelvis, obstetrics and embryology, neonatal head, and vascular. With most images updated, this second edition is completely up-to-date and highly illustrated, which when combined with an orderly, easy-to-follow structure, make this unique title unmatched in its field. Nakladatelská anotace
Keywords: ultrasonografie; radiologie, nukleární medicína a zobrazovací metody; Ultrasonography; Diagnostic Imaging; anatomie průřezová; Anatomy, Cross-Sectional; diagnostické zobrazování